Expectativas da agroindústria canavieira paranaense diante da diminuição do protecionismo no comércio internacional - Schmidtke, Claucir Roberto (2007)
The work verifies the possible reflections that a reduction in the international protectionism tends to cause in the sugar cane industry of Paraná State. The research approach was characterized by the use of the Declared Preference Techniques which presented the following results; a) increase in the area planted with sugar cane; a) increase in the number of sugar mills; c) elevation in the number of exportation by sugar mills (new productive units); d) increase in the revenue of sugar mills; e) permanence of Brazilian competitiveness. The results confirm the competitive efficiency position of this agro-Industry that tends not to suffer effects coming from the protectionism decrease, this latter being harmful to its position as world leader. It is possible to verify that a decrease in the protectionism may cause a multiple effect that will be first characterized by the elevation of the percentage of the Paraná State territory planted with sugar cane